Epidemic and Inter-epidemic Burden of Pediatric Human Parechovirus Infection in New South Wales, Australia, 2017–2018. Issue 6 (June 2020) - Khatami, Ameneh; Burrell, Rebecca; McMullan, Brendan J.; Rawlinson, William; Givney, Rodney C.; Kok, Jen; Alexandersen, Soren; Jones, Cheryl A.; Macartney, Kristine K.; Britton, Philip N.
Abstract : Background: Human parechovirus (HPeV) typically infects young children, and although infection is often asymptomatic, some types (eg, HPeV3) are associated with severe clinical manifestations, including central nervous system infection or sepsis-like syndrome, particularly affecting young infants. The third documented national epidemic of HPeV occurred in Australia in 2017–2018. Methods: Four public laboratories that perform almost all of the HPeV PCR testing in New South Wales provided data regarding HPeV tests performed from July 1, 2017 to June 30, 2018. Limited demographic and clinical data were obtained from electronic medical records for laboratory test-positive cases that presented to each of the 3 pediatric hospitals in New South Wales. Results: Five hundred eighty-one HPeV-positive samples obtained from 395 cases were included in the analysis. The peak of the outbreak occurred in late November 2017 (approximately 35 new cases each week), with the main HPeV epidemic occurring between the spring and summer months of September 2017 to January 2018; although this seasonality was observed primarily in infants less than 12 months of age. Among the 388 pediatric cases, almost half were younger than 2 months (188; 47%) and only 10 were children older than 2 years. The annualized estimated incidence of laboratory confirmed HPeV infection in children was approximately 142.4 cases per 100, 000 children younger than 5 years in New South Wales during the epidemic season. Conclusions: The large burden of HPeV infection and disease identified in young infants in this and previous Australian studies highlight the need for more comprehensive national surveillance of HPeV infections and improved prevention strategies.